2022
DOI: 10.3991/ijet.v17i13.28873
|View full text |Cite
|
Sign up to set email alerts
|

Applying Learning Analytics for Designing Effective Pedagogy for Online Courses: Analysis and Recommendations

Abstract: The countrywide lockdown since March 2020 due to COVID 19 pandemic has brought drastic changes in the Indian education system. Today, many higher education institutions offer online delivery as an alternative and/or addition to provide more flexibility to learners, specifically in the current COVID 19 Pandemic. The conventional teaching method to the technology-driven virtual mode of teaching provided opportunities with challenges to academic stakeholders. Now with the new session, discussions on the reopening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The issue of innovations in teaching natural science and technical and technological subjects with proper methodology part can be found in several foreign journals, such as [5], [6], [7], This means, the paper examines specific didactic phenomena of natural-and technological-character, with an emphasis on elementary physics, biology, ecology, and technologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of innovations in teaching natural science and technical and technological subjects with proper methodology part can be found in several foreign journals, such as [5], [6], [7], This means, the paper examines specific didactic phenomena of natural-and technological-character, with an emphasis on elementary physics, biology, ecology, and technologies.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of this paper have already published several research papers dealing with the technological innovations in teaching science-oriented subjects. Results of their previous research can be found for example in [5], [6], [7]. This research paper is unique especially because the mentioned topic of the distance form of teaching had already been investigated on a general didactic level by various authors; however, in this paper it is being examined on a specific didactic level.…”
Section: Introductionmentioning
confidence: 97%